(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Radon and its short-lived progenies contributed significantly to natural background radiation. Long-term exposure to such radiation increases the probability of lung cancer to persons. To assess the radiological hazards associated with the inhalation of radon gas from ore dust in Mazat and Kafi-Habu mining sites of Plateau, Nigeria, 12 soil samples from an abandoned tailing dump ground were collected and analysed for radon using RAD-7 electronic detector. The dose rate of each sampling point was directly measured using RADOS RDS -120 portable survey meter. The results gave a mean radon concentration ranging from 771.51 ± 21.9 Bq/m3 to 5666.13 ± 28.8 Bq/m3 with 3451.13 ± 42.9 Bq/m3as the average value for all measurements. The average concentration of measurements from Mazat and Kafi-Habu is 3671.6 ± 41.2 Bq/m3 and 3010.16 ± 46.5 Bq/m3 respectively. The average values obtained from the analysis are significantly higher than the upper limit of 300 Bq/m3 set by the International Commission on Radiological Protection (ICRP) suggesting quick remediation on the host communities. The geometrical mean value of Dose Rate (DR) and Annual Effective Dose Equivalent (AEDE) were 870 nGy/hr and 1.04 mSv/yr respectively. Again, these values are above the global average limits of 59 nGy/hr and 1 mSv/yr. The result indicates that miners working in those sites and dwellers of the study areas are at higher risk of getting exposed to radon and need to employ protective measures. This work is useful in monitoring and control of radon level for the on-site workers and the